Validating the Effectiveness of Data-Driven Gamification Recommendations: An Exploratory Study - Toda, Armando M.; Palomino, Paula T.; Rodrigues, Luiz; Oliveira, Wilk; Shi, Lei; Isotani, Seiji; Cristea, Alexandra (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2019)
Gamification design has benefited from data-driven approaches to creating strategies based on students' characteristics. However, these strategies need further validation to verify their effectiveness in e-learning environments. The exploratory study presented in this paper thus aims at verifying how data-driven gamified strategies are perceived by the students, i.e., the users of e-learning environments. In this study, we conducted a survey presenting 25 predefined strategies, based on a previous study, to students and analysed each strategy's perceived relevance, instanced in an e-learning environment. Our results show that students perceive Acknowledgement, Objective and Progression as important elements in a gamified e-learning environment. We also provide new insights about existing elements and design recommendations for domain specialists.